2019
DOI: 10.1080/21691401.2019.1657873
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The circular RNA hsa-circ-0072309 plays anti-tumour roles by sponging miR-100 through the deactivation of PI3K/AKT and mTOR pathways in the renal carcinoma cell lines

Abstract: Cao (2019) The circular RNA hsa-circ-0072309 plays anti-tumour roles by sponging miR-100 through the deactivation of PI3K/AKT and mTOR pathways in the renal carcinoma cell lines, Artificial Cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…In human intracranial aneurysms, circ 0072309 acts as a ceRNA to affect discoid domain receptor 2 and systemic amino acid transporter 2 through miR-519e-5p and miR-516b-5p [10]. In renal carcinoma, circ 0072309 exerts anti-tumor roles by sponging miR-100 [13]. In our present study, we predicted that miR-580-3p is a target of circ 0072309 by bioinformatics analysis and employed luciferase report assay and RNA pull down methods to confirm that circ 0072309 directly binds to miR-580-3p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human intracranial aneurysms, circ 0072309 acts as a ceRNA to affect discoid domain receptor 2 and systemic amino acid transporter 2 through miR-519e-5p and miR-516b-5p [10]. In renal carcinoma, circ 0072309 exerts anti-tumor roles by sponging miR-100 [13]. In our present study, we predicted that miR-580-3p is a target of circ 0072309 by bioinformatics analysis and employed luciferase report assay and RNA pull down methods to confirm that circ 0072309 directly binds to miR-580-3p.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA has circ 0072309 was identified to be located on chromosome 5 between the base sites 38523520 and 38530768 [10]. Some reports showed that has circ 0072309 was lowly expressed in breast cancer [11,12], human intracranial aneurysms [10] and renal carcinoma [13]. However, the function of has circ 0072309 in the progression of NSCLC remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…16 Several circRNAs abnormally expressed in RCC have been discovered. 11,12 For instance, circ-ZNF609 plays a ceRNA to upregulate FOXP4 level via targeting miR-138-5p in RCC. 17 Androgen receptor could promote RCC cell metastasis by targeting the circHIAT1/miR-195-5p/29a-3p/29c-3p/CDC42 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Currently, several reports also described the functions of a few circRNAs in RCC. 10,11 For example, Chen et al 12 unveiled that circ_0072309 acts as an antitumor role via targeting miR-100 through the deactivation of PI3K/AKT and mTOR signaling in RCC. In recent years, the competing endogenous RNA (ceRNA) concept proposes that circRNAs regulate gene expression through functioning as a molecular sponge of microRNAs (miRNAs), illuminating the importance of such interactions during the tumorigenic process.…”
Section: Introductionmentioning
confidence: 99%
“…Differentially, circRNA threonine-speci c protein kinase 3 (circ-AKT3) overexpression was demonstrated to decrease migrated and invaded CCRCC cells [28]. CircRNA Rap guanine nucleotide exchange factor 5 (cRAPGEF5) [29] and has_circ_0072309 [30] also impeded tumor growth and metastasis in CCRCC. In conformity with these anti-cancer circRNAs, circ_RPL23A overexpression evoked cell cycle arrest, proliferation and metastasis inhibition, and apoptosis elevation.…”
Section: Discussionmentioning
confidence: 99%